Respon Pertumbuhan Kedelai yang Diinokulasi Mikoriza pada Cekaman Ganda Alumunium dan Kekeringan - Chairani Hanum; Wahju Qamara Mugnisjah; Sudirman Yahya; Didi Soepandi; Komaruddin Idris; Asmarlaili Sahar (Jurnal Agrista, 2006)
Growth Response of Soybean with Mycorrizal Inoculation at Critical Condition of Aluminium and Draying DoubleABSTRACT. High level of aluminium in acid soil can restrict nutrient and water. Arbuscular Mycorrhizal Fungi (AMF) have been shown to decrease plant yield losses in acid soil. The objective of this study was to examine the growth responses of green house-grown soy bean colonization by AMF. The experiment was conducted at Cikabayan experimental of Bogor Agricultural University from August 2003 to February 2004. Six genotypes soy bean that result of root bioassay treated by Al by saturated (Al 25 %, Al 50 %, and Al 75 %), field capacity (80 % and 40 % FC) and Inoculated by mycorrhizae (without AMF and by AMF). Root and shoot dry matter were higher in mycorrhizal than in non mycorrhizal plants.